TRPM2 may be involved in high fructose corn syrup-induced anxiety-like behavior in adult male rats - Serhatlioglu, Ihsan; Zorlu, Gokhan; Yardimci, Ahmet; Ertugrul, Nazife Ulker; Ercan, Zubeyde; Tan, Fatih; Kelestimur, Haluk (C M B Assoc, 2023)
Excessive high fructose corn syrup (HFCS) consumption is known to cause oxidative stress, which induces transient receptor potential melastatin type 2 (TRPM2) channel gating. Oxidative stress-induced TRPM2 gating is suggested to play an important role in neurons, indicating a role for the TRPM2 channel in a variety of neuropsychiatric disorders including depression and anxiety. We investigated the effects of HFCS and chronic immobilization stress (CIS) on TRPM2 channel immunoreactivity, anxiety, and depressive-like behaviors in adult male rats. The male rats (n=8/group) were divided into 4 groups: Control, 20% HFCS (F20), 40% HFCS (F40), and stress. The control group received tap water, and F20 and F40 groups were exposed to 20% and 40% HFCS respectively for 14 consecutive days. Rats in the stress group were subjected to immobilization stress for 3 or 6 hours daily in the first and second weeks to induce CIS. Then, light/dark test, open field test (OFT), and tail suspension test (TST) were performed, respectively. In the light/dark test, the time spent in the dark chamber significantly increased in all groups vs the control group (P<0.01). In support of this result, the time spent in the light chamber significantly decreased in all groups vs the control group (P<0.01). Besides, CIS significantly increased depressive-like behavior in the stress group vs the control group (P<0.05). In serum hormone levels, corticosterone (CORT) levels significantly increased in the F40 and stress groups vs the control group (P<0.01). TRPM2 immunoreactivity significantly increased in the hippocampus, prefrontal cortex (PFC), nucleus accumbens (NaC), and amygdala regions by HFCS and CIS treatments. For the first time the present study showed that increased immunoreactivity of the TRPM2 cation channels may be linked to the anxiety-like behavior induced by HFCS.
Keywords: Anxiety; depression; high fructose corn syrup; oxidative stress; chronic immobilization stress; TRPM2